Identity and digital communication concepts, theories, practices - Cover, Rob (Routledge, 2023)
This comprehensive text explores the relationship between identity, subjectivity and digital communication, providing a strong starting point for understanding how fast-changing communication technologies, platforms, applications and practices have an impact on how we perceive ourselves, others, relationships and bodies. Drawing on critical studies of identity, behaviour and representation, Identity and Digital Communication demonstrates how identity is shaped and understood in the context of significant and ongoing shifts in online communication. Chapters cover a range of topics including advances in social networking, the development of deepfake videos, intimacies of everyday communication, the emergence of cultures based on algorithms, the authenticities of TikTok, and online communication's setting as a site for hostility and hate speech. Throughout the text, author Rob Cover shows how the formation and curation of self-identity is increasingly performed and engaged with through digital cultural practices, affirming that these practices must be understood if we are to make sense of identity in the 2020s and beyond. Featuring critical accounts, everyday examples, and analysis of key platforms such as TikTok, this textbook is an essential primer for scholars and students in media studies, psychology, cultural studies, sociology, anthropology, computer science, as well as health practitioners, mental health advocates and community members"--Provided by publisher.